Effectiveness of Giving Dragon Fruit and Fe Tablets on Increasing Hemoglobin Levels in Pregnant Women - Putri, Melia Dwi Yitna; Zahra, Tamela (Raudhah Publisher, 2024)
In 2018, the WHO reported that 41.8% of maternal deaths in developing countries were associated with anemia. Increasing hemoglobin levels can be supported by consuming fruits rich in iron, folic acid, and vitamin C, with dragon fruit being one of the beneficial options. This study aimed to assess the effectiveness of dragon fruit and Fe tablets in raising hemoglobin levels among pregnant women in Puluhan Village, Trucuk District, Klaten Regency. Utilizing a literature review approach, the study involved searches across PubMed and Google Scholar, using keywords such as